DETERMINATION OF GRAFT SUCCESS OF GRAPE CULTIVARS GRAFTED ON TWO DIFFERENT ROOSTOCKS - Oguz Dolgun; Simin Saygac Ulas; Turcan Teker (Acta Scientiarum Polonorum: Hortorum Cultus, 2016)
The aim of this study was to determine the graft performance and to follow the graft compatibility of Bornova Misketi, Trakya Ilkeren and Sultan 1 grape cultivars graft-ed on 5BB and 1103P rootstocks. Grafts were made by using omega technique. Following waxing, grafts were packed in plastic boxes filled up with fungicide humidified sawdust and chips (3:1) and were placed in callusing room (25°C, 85% relative humidity) for three weeks. Post callusing, grafts were evaluated for their callusing rate at graft union (0–4 scale), sprouting rate (%), rooting rate (%) and sapling yield (%). According to obtained data statistically significant differences were determined in all parameters except sprouting rate. Graft samples were taken each month for histological analysis during six months following callusing. No significant differences were observed among combinations in respect to histological development of graft unions. Callusing rate (3.73/5 BB–3.70/1103 P) and potted sapling yield (86.66/5 BB%–90.00/1103 P%) were the highest in Bornova Misketi among all combinations for two rootstocks.